To justify that x = 8, y = 2, and z = -5 is the solution to the system,
2x + y + 3z = 3
-3x + 3y - 2z = -8
5x - y + 5z = 13
Let's substitute the roots to the equation if it will be equivalent to the constant value. We get,
![\text{ 2x + y + 3z = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/uvvm9etihryoyhamjw1hmyyxcsv6zw5io5.png)
![2(8)\text{ + (2) + 3(-5) = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/j0sj6s9o1kz174kva3s9xih6h97gh760wl.png)
![16\text{ + 2 - 15 = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/xj7po0aqcdo6aexkbmvz4p6p8p5ocjll5e.png)
![\text{ 3 = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/7h9ungt0qgh9xu7vbs5zwk6zzq9nhnd0hf.png)
Thus, x = 8, y = 2, and z = -5 is a solution to 2x + y + 3z = 3
![-3x\text{ + 3y -2z = -8}](https://img.qammunity.org/2023/formulas/mathematics/college/tmqtb4t0skj914slwihk9bkonrreeibwqv.png)
![-3(8)\text{ + 3(2) - 29-5) = -8}](https://img.qammunity.org/2023/formulas/mathematics/college/yrw1xft2b94gv14nhbvfwbdhttjr2dkpk2.png)